Assessing Inorganic Salts for Effective Management of Late Blight Disease in Potatoes - Kassaw, Admasie; Desale, Tesfaye; Mihretie, Aderajew; Ayalew, Abebe (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Potato in Ethiopia is the primary tuber crop, and late blight poses a significant challenge to its production. Field experiments were carried out in Meket and Wadla during the 2018 and 2019 growing seasons to assess the use of salts in controlling late blight and its cost-effectiveness management strategies. The study included seven treatments: sodium bicarbonate, sodium benzoate, sodium carbonate, potassium chloride, calcium chloride, a systemic fungicide containing Mefenoxam and Mancozeb, and a control treatment. The treatments were settled in a randomized complete block design with three replications. The study found that there were significant variations in disease levels, potato tuber yield, and yield components among different treatments. Application of salts were found to be effective in reducing late blight disease, leading to higher yields. Among salts, the highest total tuber yield (23.59 and 22.02 t ha-1) was recorded from sodium bicarbonate at Meket and Wadla in 2019, respectively. The highest marginal rate of return (2,852%) was obtained from synthetic fungicide followed by 2,634% by sodium bicarbonate. Therefore, besides synthetic fungicide, foliar application of sodium bicarbonate can decrease potato late blight disease pressure and is advised to be considered as an alternative control measure.